Hierarchical Cu-ZIF-8 anchored 3D carbon graphite felt for enzyme-less electrochemical sensing of malathion residue - Xiao, Li; Alghodran, Musab Ahmad; Zainol, Nurul Izzah; Miskam, Mazidatulakmam; Alang Ahmad, Shahrul Ainliah; Abdul Aziz, Siti Fatimah Nur (Elsevier, 2026)
Detection of organophosphate pesticides remains a significant analytical challenge, with current methods, including electrochemical sensors, still constrained by performance and practical-use limitations. Most existing systems rely on unstable enzymes or nanomaterials that require complex or chemically harsh synthesis routes. Emerging non-enzymatic, green-synthesized MOF-based sensors offer high surface area and tunable structures, but their poor conductivity and limited evaluation with real samples continue to restrict practical use. Herein, we report a copper(II)-doped zeolitic imidazolate framework-8 (Cu-ZIF-8)-based sensor, synthesized via a simple aqueous, room-temperature method, capable of directly detecting commercially formulated malathion. The Cu-ZIF-8 composite was anchored onto a three-dimensional graphite felt (GF) substrate, forming a hierarchical electrode (Cu-ZIF-8/GF) with preserved polyhedral morphology and excellent structural integrity, as confirmed by comprehensive physicochemical characterization. The introduction of Cu2+ into the ZIF-8 framework successfully enhances its electrochemical conductivity properties, as evidenced by the enhanced current response observed in cyclic voltammetry (CV). Electrochemical measurements using differential pulse voltammetry (DPV) demonstrated that the Cu-ZIF-8/GF electrode enabled sensitive detection and promising selectivity of the organophosphate pesticide malathion, with a broad linear response range from 10−6 to 10−2 M (R2 = 0.9952) and a low detection limit of 0.90 μM. The sensor exhibited excellent recovery rates ranging from 97% to 104% in vegetable wash samples. The results were in strong agreement with those obtained via high-performance liquid chromatography (HPLC), highlighting the sensor's reliability. Notably, this study is among the first to utilize commercial-grade malathion pesticide rather than purified analytical standards, highlighting the practical applicability of the enzyme-free metal-doped MOF-based electrochemical sensor.